ANALYSIS OF FACTORS THAT INFLUENCE FARMERS' DECISIONS IN CONTINUING ARABICA COFFEE FARMING IN PEMATANG SIDAMANIK VILLAGE, PEMATANG SIDAMANIK DISTRICT, SIMALUNGUN REGENCY - Wildani Lubis; Syahbani Alfaizar Nababan (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Pematang Sidamanik Village, located in Pematang Sidamanik Subdistrict, Simalungun Regency, is one of the areas known as a center for Arabica coffee production in North Sumatra. A phenomenon of concern is the declining interest of farmers, especially the younger generation, in continuing coffee farming. As a result, many coffee farmers are forced to switch to other jobs to meet their families' needs. This trend threatens the sustainability of Arabica coffee production in Pematang Sidamanik Village. This study aims to identify the factors influencing farmers' decisions in Pematang Sidamanik Village and to examine farmers' decisions regarding the continuation of Arabica coffee farming in the village. The research methodology employs a quantitative descriptive approach with binary logistic regression analysis. The sample was selected using simple random sampling, with a total of 42 Arabica coffee farmers. The results indicate that selling price and income have a positive and significant influence on farmers' decisions to continue Arabica coffee farming in Pematang Sidamanik Village. This is due to relatively stable and normal selling prices, ranging from IDR 30,000 to IDR 36,500 per kilogram. Additionally, the higher the income received by farmers, the greater their tendency to maintain or continue their Arabica coffee farming. A survey of 42 respondents showed that 54.8% of farmers decided to continue Arabica coffee farming in Pematang Sidamanik Village. Some factors influencing this decision include the hilly terrain, which is suitable for Arabica coffee cultivation, ease of plant maintenance, and stable selling prices and income. Keywords: Farmer Decision, Arabica Coffee, Coffee Farming.